+0  
 
0
649
1
avatar

-20t²+23bt-6b²

 05.07.2017
 #1
avatar+8576 
0

in klammern???

-20t²+23bt-6b²

 

\({\color{red}-20\ t²+23b\ \cdot t-6b² }=0=(-20)\cdot(t-t_1)\cdot (t-t_2)\)

.   a           b                c

 

\(t = {-b \pm \sqrt{b^2-4ac} \over 2a}\)

 

\(t = {-23b \pm \sqrt{23^2\cdot b^2-4\cdot ( -20) \cdot (-6b^2)} \over -40}\)  

 

\(t=\frac{-23\pm \sqrt{529b^2-480b^2}}{-40}\)

 

\(t=\frac{-23b\pm \sqrt{49b^2}}{-40}\)

 

\(t=\frac{-23b\pm 7b}{-40}\)

 

\(t_1=\frac{2}{5}b\)   

 

\(t_2=\frac{3}{4}b\)

 

\(-20\ t²+23b\ \cdot t-6b²=(-20)\cdot(t-\frac{2}{5}b)\cdot (t- \frac{3}{4}b)\) 

 

laugh  !

 05.07.2017
bearbeitet von asinus  05.07.2017
bearbeitet von asinus  05.07.2017
bearbeitet von asinus  05.07.2017
bearbeitet von asinus  06.07.2017

3 Benutzer online